(untitled) (Perner’s Contacts, 2016)
The tribotechnical diagnostics (TTD) use lubricants as media that help obtain information about processes and changes in the systems that they lubricate. The methods TTD are used to determine optimum regular interval for oil exchange. The paper deals with possibilities of using modern instrumental methods in particular: infrared spectrometry with Fourier transformation (FTIR spectrometry), atomic emission spectrometry (AES) and analysis on particle counters for optimalization of change interval of engine oil.